(untitled) (International Journal of Criminology and Sociology, 2025)
The article examines the recent developments in the European Union’s regulation concerning crypto-assets. This regulation is evolving in a fragmented manner and by sectors, particularly focusing on markets and the financial sector in general, and does not have a defined perspective for a comprehensive regulation of the sector. It is a regulation that aims to introduce elements of public control over the actors in the system to regulate the markets and also in anticipation of future new instruments consisting of crypto-assets, introducing elements of public control entrusted to national authorities (notably Regulation 2023/1114 and 2022/858). Meanwhile, in order to enhance the fight against money laundering, elements of control and verification on intermediaries have been introduced as part of the AML Package (particularly with Regulation 2023/1113), imposing obligations on them and implementing control tools over end users, their identities, and their operations. National legal systems are gradually receiving these regulations and harmonizing with European Union law.